Long-term electroacupuncture for low anterior resection syndrome in postoperative rectal cancer patients: case reports - Li, Wenna; Yang, Ming; Huang, Jinchang; Zhang, Qiaoli (Frontiers in Medicine, 2025)
This study reports two cases of rectal cancer patients who developed low anterior resection Syndrome (LARS) following rectal cancer surgery. Both patients presented with significant bowel dysfunction, including frequent defecation, urgency, fecal incontinence, and incomplete evacuation. Current treatments for LARS are limited by variable responses, high costs, and adherence issues, highlighting the need for practical, safe therapies with minimal side effects. The patients underwent a 6-month electroacupuncture treatment targeting Baliao points. Assessments were conducted using the LARS score, Wexner fecal incontinence score, and the EORTC QLQ-C30 scale. Results indicated a marked reduction in bowel frequency, significant relief of fecal incontinence symptoms, and improvement in overall health status and quality of life. In addition, emotional and cognitive functions were enhanced. These case reports suggest that electroacupuncture may be a valuable adjunctive treatment for managing LARS and improving patient emotional status and quality of life. Further high-quality research is necessary to evaluate the long-term efficacy of this treatment fully.